Banking on a religious divide: Accounting for the success of the Netherlands' Raiffeisen cooperatives in the crisis of the 1920s - Christopher L. Colvin (Queen's University Centre for Economic History (QUCEH), 2017)
This article investigates the impact of the socioreligious segregation of Dutch society on the asset allocation choices of rural bankers and the withdrawal behavior of their depositors during the early 1920s. Results suggest that cooperatively-owned Raiffeisen banks for both Catholic and Protestant minority groups could limit their exposure to a debt-deflation crisis, despite operating more precarious balance sheets than banks for majorities. Business histories demonstrate how strict membership criteria and personal guarantors acted as screening and monitoring devices. Banks serving minorities functioned as club goods, managing their exposure to the crisis by exploiting the confessionalized nature of Dutch society.
Keywords: G01; G21; N24; N84; P13; Z12; 330; cooperative banking; club goods; financial history; the Netherlands